INVESTMENT RISK OF SOLO-NGAWI TOLL ROAD - Zaid Dzulkarnain Zubizaretta; Rudy Hermawan Karsaman; R. Sony Sulaksono Wibowo (CI-TECH, 2021)
In investing, there is definitely a risk, as well as the concession of toll roads. Risk analysis is used to anticipate losses due to an element of risk at each investment stage. The results of the analysis show that the highest risk probability for the Solo-Ngawi toll road is land availability and the influence of weather during development and the highest risk impacts are land availability, the potential for revolution in state governance. Based on the results of the analysis, the investment risk level of the Ngawi Solo Toll Road is included in the moderate risk category, so there is a need for cooperation in risk assurance by the Insurance Agency so that the risk level can be reduced to be lower than before.